The Character Education in the Book of Hikam and Its Relevance to the National Character Education Program in Indonesia - Aulia Suhesty; Diah Rahayu; Annisa Lyona (Jurnal Madania)
This study aimed to explain the concept of character education contained in the book of Hikam and its relevance to Indonesia's national character education program. This research had been library research that used the content analysis technique. The data collection technique used the documentation technique. The findings in this study were that the concept of character education in the book of Hikam had been religious character education which refers to the character of Uluhiyyah (divinity), namely, humans must orient all their life activities to God by spreading goodness wherever they are. The closer and more obedient a person is to his God, the more character and noble that person will be. This religious education is an exercise (riyadhah) and sincerity (mujahadah) that is planned and systematic and carried out by an educator to form a pious personality in a student physically and spiritually. The concept of religious character refers to faith, honesty, piety, sincerity, and patience. Religious character educates a human being to become a person of character and responsibility. The character education values in the book of Hikam strengthen Indonesia's national character education program. In Sheikh Ibn Atha'illah's view, the character education strategy is divided into two stages: planting and spreading. Religious education is very relevant to the national character education strategy, namely intervention (instilling character in students) and habituation (instilling character through the environment).